Pengembangan Pembelajaran IPS (Ilmu Pengetahuan Sosial) di SD/Mi Berbasis Integrasi Interkoneksi - Lisnawati Lisnawati (Jurnal Al-Muta`aliyah : Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2018)
Orientation parsialistik education will hurt students, because they just have a tendency to know a lot of things but very less value system. Such circumstances resulted, educates students to have a personality that is not balanced, aspects of their way of life evolved, but aspects of life attitude and life skills are underdeveloped. The imbalance will form a protégé as a figure certain material specialist who lack a sense of awareness of the existence of the surrounding environment and are quite prone to distortion value growth. Learning Social Sciences (IPS) based interconnect integration has become an alternative to the creation of a generation of intelligent and noble who understand the purpose of human life in an integrated and comprehensive.